Analysis of Ecoliteracy Based Science Learning Resources Needs to Realize SDGs - Rilianti, Adhy Putri; Huda, M. Misbachul (Science Education and Application Journal, 2023)
This research aimed to describe needs of students’ Science learning resources with ecoliteracy at PGSD STKIP Al Hikmah Surabaya. Students, the majority of whom are young, have great potential to realize a more environmentally friendly Indonesia as stated in the Sustainable Development Goals. Research method that is used in this research was qualitative. Data collected by using questionnaires and interviews. Data analyzed descriptively. Research revealed that PGSD students have middle ecoliteracy . Science learning resource that is needed for students was the Science Education Book with Ecoliteracy . Through the development of Ecoliteracy -based Science Education Books, it is hoped that PGSD students will be able to become students who understand and are aware of environmental issues (ecoliterate), and can design learning activities for elementary students that can instill environmental care characters. The book consisted of information about ecoliteracy and teaching and learning in elementary school for enhancing students’ ecoliteracy. The book was also completed with youtube, instagram, and journal links as an additional information.This research aimed to describe needs of students’ Science learning resources with ecoliteracy at PGSD STKIP Al Hikmah Surabaya. Students, the majority of whom are young, have great potential to realize a more environmentally friendly Indonesia as stated in the Sustainable Development Goals.Research method that is used in this research was qualitative. Data collected by using questionnaires and interviews. Data analyzed descriptively. Research revealed that PGSD students have middle ecoliteracy . Science learning resource that is needed for students was the Science Education Book with Ecoliteracy .Through the development of Ecoliteracy -based Science Education Books, it is hoped that PGSD students will be able to become students who understand and are aware of environmental issues (ecoliterate), and can design learning activities for elementary students that can instill environmental care characters. The book consisted of information about ecoliteracy and teaching and learning in elementary school for enhancing students’ ecoliteracy. The book was also completed with youtube, instagram, and journal links as an additional information.